Energy efficiency procedures for agricultural machinery used in onion cultivation (Allium fistulosum) as an alternative to reduce carbon emissions under the clean development mechanism at Aquitania (Colombia) (2014)
Climate change has both causes and consequences over agriculture. This paper focuses on the first element and presents scenarios for ASOLAGO -an onion cropper's association in Colombia with 250 members- to reduce their carbon footprint. It evaluates a case study at "La Primavera" farm using a methodology approved by the United Nations Framework Convention on Climate Change. Land preparation and crop irrigation were analyzed as stages in order to propose energy efficiency alternatives for both the farm and the association. They include field efficiency, fuel economy and energy efficiency from biofuels for the first stage as well as solar and wind energy supply for the second. A cost-benefit analysis to generate additional income selling additional power produced by the system to the National Grid was done.